The given differential equation is
The auxiliary equation is "m^2+m-2=0."
"\\therefore \\ m^2+m-2=0"
"\\implies m^2+2m-m-2=0"
"\\implies m(m+2)-1(m+2)=0"
"\\implies (m+2)(m-1)=0"
"\\implies m=1,-2" .
"\\therefore \\ C.F.=Ae^x+Be^{-2x}"
Where ,"C.F.=" Complementary Function.
Now ,
"P.I.=\\frac{1}{D^2+D-2}(-6sin2x-18cos2x)""=\\frac{1}{D^2+D-2}(-6sin2x)+\\frac{1}{D^2+D-2}(-18cos2x)""=-6\u00d7\\frac{1}{-2^2+D-2}sin2x-18\u00d7\\frac{1}{-2^2+D-2}cos2x""=-6\u00d7\\frac{1}{D-6}sin2x-18\u00d7\\frac{1}{D-6}cos2x""=-6\u00d7\\frac{D+6}{D^2-36}sin2x-18\u00d7\\frac{D+6}{D^2-36}cos2x"
Multiplying numerator and denomination by "D+6" .
"=\\frac{3}{20}\u00d7(D+6)sin2x+\\frac{9}{20}\u00d7(D+6)cos2x"
"=\\frac{3}{20}\u00d7(2cos2x+6sin2x)+\\frac{9}{20}\u00d7(-2sin2x+6cos2x)"
"=cos2x(\\frac{3}{10}+\\frac{27}{10})+sin2x(\\frac{9}{10}-\\frac{9}{10})"
"=3cos2x"
Therefore the complete solution is
"y=C.F.+P.I"
"=Ae^x+Be^{-2x}+3cos2x..............(1)"
Again differentiate equation (1) ,we get
"y'(x)=Ae^x-2Be^{-2x}-6sin2x \\ ....................(2)"
As given that ,
"y(0)=2 \\ and \\ y'(0)=2"
So from equation (1) and (2) ,we get
"A+B+3=2"
"\\implies A+B=-1 \\ ..............(3)"
and "A-2B=2....................(4)"
Subtracting (4) from (3) ,we get
"A+B-(A-2B)=-1-2"
"\\implies 3B=-3 \\ \\implies B=-1"
Again from (3) ,we get
"A-1=-1 \\ \\implies A=0" .
Therefore equation (1) become
"y=-e^{-2x}+3cos2x" .
Comments
Leave a comment